PEMBELAJARAN MATAPELAJARAN BIOLOGI MATERI LINGKUNGAN DI SEKOLAH MENGENGAH ATAS DAN DAYA DUKUNGNYA TERHADAP LITERASI LINGKUNGAN SISWA - Prasetiyo Prasetiyo (Florea : Jurnal Biologi dan Pembelajarannya, 2017)
The purpose of this study is to know the learning and the carrying capacity of environmental literacy on the subject of environmental biology at Senior High School, apply the type of qualitative research and use purposive sampling in sampling, data collection by questioner and interview. The results showed that the learning done by the teacher has not fully supported the optimization of students' literacy.